Criando mensagens secretas na escola básica utilizando a criptografia – RSA - Castro Junior, Waldir Claudio de (Universidade Federal de São Carlos, 2015)
Cryptography is a fascinating topic, concerning the practical point of view, and it is useful to access bank accounts, e-mails and social networks. According to this perspective, this study aimed to show how simple it may be to make use of cryptography. It was proved, through the work performed, that it is possible for students from elementary and high school to encrypt and decrypt messages using R.S.A. Cryptography, which involves the concept of creating public keys and private keys for the encryption of messages. A simple but powerful activity on the utility view was assigned to show students from the 9th grade of elementary school and from the 1st and 2nd years of high school from a private school in São Paulo State how interesting and pleasurable the use of Mathematics can be. Such activities are not usually present in the traditional didactic materials. The theoretical tools, containing theorem and corollaries, as well as their demonstrations, which mathematically justify the validity of techniques and the algorithm used on R.S.A. Cryptography will be presented. The activities do not assume sophisticated prerequisites and can be applied in the classroom, in real situations, so that the students can appreciate the beauty of Mathematics.
Keywords: Matemática - estudo e ensino; Criptografia; Matemática aplicada; R.S.A. cryptography; Public keys; Private keys; Applications of mathematics in teaching; CIENCIAS EXATAS E DA TERRA::MATEMATICA